2011
DOI: 10.1161/hypertensionaha.111.177071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resistance Training on Blood Pressure and Other Cardiovascular Risk Factors

Abstract: Abstract-We reviewed the effect of resistance training on blood pressure and other cardiovascular risk factors in adults.Randomized, controlled trials lasting Ն4 weeks investigating the effects of resistance training on blood pressure in healthy adults (age Ն18 years) and published in a peer-reviewed journal up to June 2010 were included. Random-and fixed-effects models were used for analyses, with data reported as weighted means and 95% confidence limits. We included 28 randomized, controlled trials, involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
233
4
17

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(268 citation statements)
references
References 48 publications
14
233
4
17
Order By: Relevance
“…For example a meta-analysis showed significant decrease in blood pressure, body fat and triglycerides in groups of normotensive or prehypertensive adults by dynamic resistance training [60]. In a Cochrane review Orozco et al [61] concluded that exercise plus diet reduced risk of diabetes compared to standard recommendations and had favorable effects on weight, BMI, waist-to-hip-ratio, waist circumference, and systolic as well as diastolic blood pressure but only marginal effects on blood lipids.…”
Section: Exercise Physical Activity and Cardiovascular Effectsmentioning
confidence: 99%
“…For example a meta-analysis showed significant decrease in blood pressure, body fat and triglycerides in groups of normotensive or prehypertensive adults by dynamic resistance training [60]. In a Cochrane review Orozco et al [61] concluded that exercise plus diet reduced risk of diabetes compared to standard recommendations and had favorable effects on weight, BMI, waist-to-hip-ratio, waist circumference, and systolic as well as diastolic blood pressure but only marginal effects on blood lipids.…”
Section: Exercise Physical Activity and Cardiovascular Effectsmentioning
confidence: 99%
“…The studies to date have been largely unconvincing and in this light a recent meta-analysis of resistance training on BP and other cardiovascular risk factors is very welcome. 42 The studies included in the analysis were generally quite small (28 studies, 33 study groups, 1012 participants) and the exercise intervention varied and further division of the studies by patient characteristics or type of exercise is fraught. However, on average, the intervention groups had BP that was ≈4/4 mm Hg lower than controls in normotensive and prehypertensive study groups.…”
Section: Resistance Exercise and Bpmentioning
confidence: 99%
“…On the other hand, current evidence suggests that low-to moderate-intensity resistance training does not effect on arterial stiffening [36][37][38]. Interestingly, resistance training results in decreased blood pressure as a training adaptation despite increases in blood pressure during exercise [39]. These suggest that the resistance training-related factors contributing to arterial stiffness are complex and the physiological mechanism underlying the effects of resistance training on vascular function is not yet well-understood.…”
Section: Discussionmentioning
confidence: 94%